The TNF-β Gene Nco I Polymorphism Is Not Associated with Hypertriglyceridemia or Insulin Resistance in Lean and Obese Subjects - Fernandez-Real, J.M.; Gutierrez, C.; Ricant, W.; Casamitjana, R. (Biochemical and biophysical research communications, 1997)
Interindividual differences in TNF-α monocyte responses can be accounted for by genetic polymorphisms at the TNF-β locus defined by theNco Irestriction enzyme. Higher triglyceride levels in non-insulin-dependent diabetic patients homozygous at the 10.5-kb fragment of the TNF-β gene have been described. The aim of this study was to investigate whether the Ncol polymorphism of the TNF-β gene influences the relationship between insulin resistance and triglyceride levels. Thirty-eight healthy volunteers were divided into two groups according to the absence [homozygous for class 1 allele (1/1), n=16] or presence of the class 2 allele [n=22; 19 heterozygous (1/2), and 3 homozygous (2/2)]. Both groups were comparable in sex, age, BMI, waist/hip ratio, fat mass and percentage of body fat as measured by bioelectric impedance, skinfold measurements, and blood pressure (all p>0.05). There were no differences in serum cholesterol (total, or HDL and VLDL fractions) or in total or VLDL triglycerides between the groups (all p>0.05). The insulin sensitivity index (Minimal Model method) was comparable for the two groups. In summary, the 10.5-kb homozygous genotype of the TNF-β locus does not contribute to differences in triglyceride levels or insulin sensitivity among nondiabetic subjects.